Ketahanan Ekonomi Keluarga : Analisis Multidimensi Faktor Penentu di Dusun Beringin Barat, Labuhan Ratu V, Lampung Timur - Synthia Puspitasari; Nur Syamsiyah (Journal Economic Excellence Ibnu Sina, 2025)
Family economy is an important aspect in improving community welfare, especially in rural areas. This study aims to determine the effect of education level and income on family economy. The method used is quantitative descriptive with a population of heads of families in Dusun Beringin Barat, Labuhan Ratu V, East Lampung. The sample consisted of 50 respondents, determined through the Slovin formula with a simple random sampling technique. The results of the t-test showed that education level did not have a significant effect on family economy (sig. 0.317> 0.05 and t count -1.011 <2.0106). On the other hand, income had a significant effect (sig. 0.000 <0.05 and t count 4.497> 2.0106). Simultaneously, education and income had an effect on family economy, as evidenced by the F test (F count 15.783> F table 3.190727).